PAEDIATRIC PROJECT ECHO: EXPLORING THE EDUCATIONAL NEEDS OF ONTARIO HEALTHCARE PROVIDERS WITH INTEREST IN CARING FOR CHILDREN WITH MEDICAL COMPLEXITY. (18th May 2018) - Marcinko, Josip; Orkin, Julia; Cohen, Eyal; Ho, Michelle; Lalloo, Chitra; Jiwan, Annie; McKillop, Adam; Kulandaivelu, Yalinie; Stinson, Jennifer
Abstract: BACKGROUND: Project ECHO® is an innovative, interactive model for medical education and healthcare delivery that expands access and capacity to provide evidence-informed care. This model virtually connects specialist interprofessional teams with community healthcare providers (HCPs). It aims to increase knowledge, build capacity, and ultimately, improve patient outcomes by bringing expertise to the community. This project focuses on the first paediatric implementation of Project ECHO for children with medical complexity. This is the first Project ECHO for this population. OBJECTIVES: In preparation for this novel program launch in January 2018, a needs assessment was conducted with the objectives of: (1) informing the complex care-specific ECHO curriculum; and (2) assessing community partner preferences for program format and delivery modality. DESIGN/METHODS: An online survey (38 items; 15-minutes) was distributed via targeted emails to professional networks, associations, and allied health organizations related to complex care throughout Ontario. The survey assessed interest in specific educational topics as well as program format preferences. An online survey and data management tool (REDCap) was used to build the survey and ensure data quality and security. RESULTS: 49 HCPs completed the survey for Paediatric Project ECHO for Children with Medical Complexity . Profession breakdown was: 29% paediatricians, 19% dieticians, 16% nurses, 14% nurse practitioners with the remaining being allied health care professionals, including occupational therapists, social workers and psychologists. Overall, 39% of participants practiced in academic hospitals, 27% in non-academic hospitals, and 35% in other community settings. In terms of program format, 63% preferred weekly 1- or 2-hour educational sessions versus longer sessions. Top medical topics rated by HCPs were: management of nutrition, pain or irritability of unknown origin, and challenging behaviours in children with complex care needs. Other topics of interest included: developmental review, transition to adult care, advanced care planning, funding opportunities, and social supports for the patient as well as caregivers and siblings. CONCLUSION: HCPs who expressed interest in Paediatric Project ECHO for Children with Medical Complexity are generally experienced professionals who preferred short educational sessions. The themes that emerged from this needs assessment spanned the biological, psychological and social domains of management of complex care patients. Survey results are being used to inform the development of an evidence-based paediatric complex care curriculum that meets the needs of community HCPs. This project is funded by the MOHLTC.